PENGARUH FASILITAS DAN AKSESIBILITAS TERHADAP MINAT BERKUNJUNG WISATAWAN AIR TERJUN CURUG PAPAT KABUPATEN REJANG LEBONG - Dwi Kurniawan; Mardhiyah Dwi Ilhami (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to find out the Effect of Facilities and Accessibility on Tourists' Interest in Visiting Curug Papat Waterfall, Rejang Lebong Regency. This type of research is a quantitative descriptive study. The population of this study was visitors to the Curug Papat Waterfall in Rejang Lebong Regency as the research object. The data collection technique used observation, interview, and questionnaire. The data analysis technique used descriptive analysis, inferential analysis by using SPSS and analysis of the coefficient of determination (R2). The results of this study indicate that facilities have a positive effect on tourists' interest in visiting Curug Papat Waterfall, Rejang Lebong Regency. This means that the more optimal the facilities available at Curug Papat Waterfall, the higher the level of tourist interest in visiting. Accessibility has a positive effect on tourists’ interest in Visiting Curug Papat Waterfall, Rejang Lebong Regency. The higher the quality of accessibility perceived by tourists, the higher the level of interest in visiting. Facilities and accessibility simultaneously or together have a positive and significant effect on tourists’ interest in visiting Curug Papat Waterfall, Rejang Lebong Regency. This means that if the level of facilities and accessibility is high, it will increase tourists’ interest in visiting. Keywords: accessibility, facilities, visiting interest